STUDY OF MARINE STRUCTURAL CORROSION USING CORROSION COUPONS IN LUMUT AREA - Potty, Narayanan Sambu; Ting, Ong Shiou; Liew, M.S. (Malaysian Journal of Science, 2011)
The corrosion rate in marine environments affects economic interest since the loss of steel in marine structures has impact on structural safety and performance. With emphasis to maintain existing structures in service, there is increasing interest in predicting corrosion rate at a given location for a given period of exposure. Corrosion allowances are prescribed for structural members by standards based on the corrosion protection provided, expected rate of corrosion and service life of structure. There are no studies to determine the appropriate corrosion allowance for marine steel structures in Malaysia. The research objectives are to determine the nature and rate of corrosion and the effect of differences in the immersion depth and microalgae on the corrosion rate. Two sets of corrosion coupons of Type 3 Steel consisting of mild steel were immersed in seawater at Lumut in Malaysia. The corrosion rate of the coupon is estimated based on the material weight loss with time. The corrosion rate is controlled by oxidation in short term and bacterial activity in long term. Corrosion rate in the immersion zone is observed to be more than in the splash zone. The results are also compared with code prescriptions and discussed. (Keywords: rate of corrosion, uniform corrosion, pitting, corrosion coupons, marine structures.)